Re-discovering a landscape: the barrow and motte in north Ayrshire - Linge, John (Proceedings of the Society of Antiquaries of Scotland, 1988)
There is a need to reassess large mounds currently interpreted as mottes in the light of the possibility that they are burial mounds. A R